Study on How Impact of Foreign Direct Investment on Logistics Transport Development: HCM, Vietnam Case - Hanh, Vu Thi Kim (Modern Perspectives of Logistics Transport in Economics. Empirical Studies in Ho Chi Minh, Vietnam Vol. 2, 2021)
Foreign Direct Investment (FDI) has a significant impact on an economy, particularly in developing countries such as Vietnam. FDI has a strong and deep impact on almost all economic sectors in a country. The goal of this paper is to use multivariate regression to assess the impact of IDF on logistics transport development in Ho Chi Minh City, Vietnam (HCM). The important findings are that, while registered FDI capital and the number of FDI projects have an impact, operating FDI capital has no impact on freight productivity calculated on labour in the logistics transport industry (LTI). While number of FDI projects and operating FDI capital impact, registered FDI capital does not impact on productivity of passenger that calculated on labour in LTI. While registered FDI capital and the number of FDI projects have an impact, operating FDI capital has no impact on freight productivity, which is calculated using capital in LTI. While registered FDI and operating FDI have an impact, the number of FDI projects has no effect on GDP.